Modeling the Influence of Cognitive, Motor, and Affective Factors on Early Math Communication - Aisyah, Siti; Syarah, Erie Siti; Novita, Dian; Setiawan, Eko (JURNAL PENDIDIKAN USIA DINI, 2026)
Learning Mathematical communication is essential for early cognitive development, yet few studies have examined how multiple developmental factors influence this skill simultaneously. This study explores the extent to which conceptual understanding, motor skills, and learning enthusiasm affect mathematical communication in early childhood. A total of 159 children aged 4–6 years from six Early Childhood Education (ECE) institutions in Java and Bali participated in the study. An explanatory quantitative method was applied using a one-group pretest-posttest design. A Likert-scale questionnaire measured four latent variables: conceptual understanding, motor skills, learning enthusiasm, and mathematical communication. Data were analyzed using Structural Equation Modeling (SEM) with LISREL. Confirmatory Factor Analysis showed good model fit with all loading factors above 0.50 and construct reliability above 0.70. The results demonstrated that all three variables significantly influenced children's mathematical communication skills, with motor skills having the greatest impact. Additional qualitative data from teacher journals, observations, and interviews provided deeper insights into how movement, interaction, and motivation contribute to children’s ability to express mathematical ideas. This study underlines the importance of integrating cognitive, physical, and affective aspects in early math learning. The research is limited by its short duration and localized sample. Further studies should consider broader contexts and long-term implementation